Lipid for biodiesel production from attached growth Chlorella vulgaris biomass cultivating in fluidized bed bioreactor packed with polyurethane foam material. (September 2017) - Mohd-Sahib, Ainur-Assyakirin; Lim, Jun-Wei; Lam, Man-Kee; Uemura, Yoshimitsu; Isa, Mohamed Hasnain; Ho, Chii-Dong; Kutty, Shamsul Rahman Mohamed; Wong, Chung-Yiin; Rosli, Siti-Suhailah
Highlights: Thermodynamic favorability in selecting fluidized beds' support material. Polyurethane foam for growing attached microalgae Chlorella vulgaris biomass. Determination of suitable harvesting period of attached microalgae biomass. Polyurethane foam of 1.00-mL cubes achieved the highest biomass and lipid weights. FAME composition of harvested microalgae biomass complied with biodiesel standards. Abstract: The potential to grow attached microalgae Chlorella vulgaris in fluidized bed bioreactor was materialized in this study, targeting to ease the harvesting process prior to biodiesel production. The proposed thermodynamic mechanism and physical property assessment of various support materials verified polyurethane to be suitable material favouring the spontaneous adhesion by microalgae cells. The 1-L bioreactor packed with only 2.4% (v/v) of 1.00-mL polyurethane foam cubes could achieve the highest attached growth microalgae biomass and lipid weights of 812 ± 122 and 376 ± 37 mg, respectively, in comparison with other cube sizes. The maturity of attached growth microalgae biomass for harvesting could also be determined from the growth trend of suspended microalgae biomass. Analysis of FAME composition revealed that the harvested microalgae biomass was dominated by C16-C18 (>60%) and mixture of saturated and mono-unsaturated fatty acids (>65%), satiating the biodiesel standard with adequate cold flow property and oxidative stability.